The role of tax socialization in tax digitalization and taxpayer awareness on individual taxpayer compliance - Made Inatamayu Ardika; Nyoman Sentosa Hardika; Anak Agung Putri Suardani (Journal of Applied Sciences in Accounting, Finance, and Tax, 2023)
This study aims to assess the impact of tax digitalization and taxpayer awareness on the compliance of individual taxpayers, with tax socialization serving as a moderating factor. The research involves the analysis of primary data gathered from questionnaires distributed to 100 individual taxpayers registered at the Kantor Pelayanan Pajak (KPP) Denpasar Barat, utilizing probability sampling techniques for sample selection. The study employs the Partial Least Square (PLS) method through the SmartPLS 4 application to evaluate the variables. The findings of this investigation reveal that tax digitalization significantly enhances individual taxpayer compliance. Moreover, taxpayer awareness also exhibits a positive and substantial influence on individual taxpayer compliance. Notably, tax socialization is found to strengthen the connection between tax digitalization and individual taxpayer compliance. Furthermore, it moderates the relationship by mitigating the impact of taxpayer awareness on individual taxpayer compliance. What sets this study apart is its holistic approach: while previous research has often explored the isolated impacts of tax digitalization and taxpayer awareness on compliance, our study introduces the concept of "tax socialization" as a moderating variable. This novel inclusion delves into the mechanisms by which informing and educating taxpayers about tax-related matters can influence compliance within the digitalization context.